Physical exercise in Aging: Nine weeks of leg press or electrical stimulation training in 70 years old sedentary elderly people - Sandra Zampieri; Simone Mosole; Stefan Löfler; Hannah Fruhmann; Samantha Burggraf; Ján Cvečka; Dušan Hamar; Milan Sedliak; Veronica Tirptakova; Nejc Šarabon; Winfried Mayr; Helmut Kern (PAGEPress Publications, 2015)
Sarcopenia is the age-related loss of muscle mass and function, reducing force generation and mobility in the elderlies. Contributing factors include a severe decrease in both myofiber size and number as well as a decrease in the number of motor neurons innervating muscle fibers (mainly of fast type) which is sometimes accompanied by reinnervation of surviving slow type motor neurons (motor unit remodeling). Reduced mobility and functional limitations characterizing aging can promote a more sedentary lifestyle for older individuals, leading to a vicious circle further worsening muscle performance and the patients' quality of life, predisposing them to an increased risk of disability, and mortality. Several longitudinal studies have shown that regular exercise may extend life expectancy and reduce morbidity in aging people. Based on these findings, the Interreg IVa project aimed to recruit sedentary seniors with a normal life style and to train them for 9 weeks with either leg press (LP) exercise or electrical stimulation (ES). Before and at the end of both training periods, all the subjects were submitted to mobility functional tests and muscle biopsies from the Vastus Lateralis muscles of both legs. No signs of muscle damage and/or of inflammation were observed in muscle biopsies after the training. Functional tests showed that both LP and ES induced improvements of force and mobility of the trained subjects. Morphometrical and immunofluorescent analyses performed on muscle biopsies showed that ES significantly increased the size of fast type muscle fibers (p<0.001), together with a significant increase in the number of Pax7 and NCAM positive satellite cells (p<0.005). A significant decrease of slow type fiber diameter was observed in both ES and LP trained subjects (p<0.001). Altogether these results demonstrate the effectiveness of physical exercise either voluntary (LP) or passive (ES) to improve the functional performances of aging muscles. Here ES is demonstrated to be a safe home-based method to counteract fast type fiber atrophy, typically associated with aging skeletal muscle.